Enterovirus myocarditis as a cause of neonatal collapse. Issue 5 (20th August 2004) - Inwald, D; Franklin, O; Cubitt, D; Peters, M; Goldman, A; Burch, M
Abstract : Seven neonates required intensive care at our institution with enterovirus myocarditis, 2001–2003. Presentation was at a median age of 9 days. All had ischaemic electrocardiograms, poor ventricular function, raised creatine kinase, and enterovirus RNA detected by reverse transcriptase polymerase chain reaction. Four survived. Enterovirus myocarditis may be an under recognised cause of neonatal collapse.